The Neumann Problem for a Multidimensional Elliptic Equation with Several Singular Coefficients in an Infinite Domain - Ergashev, T. G.; Tulakova, Z. R. (Lobachevskii journal of mathematics, 2022)
In this article the Neumann problem for a multidimensional elliptic equation with several singular coefficients in the infinite domain is studied. Using the method of the integral energy, the uniqueness of solution is proved. In proof of existence of the explicit solution of the Neumann problem a differentiation formula, some adjacent and limiting relations for the Lauricella hypergeometric functions and the values of some multidimensional improper integrals are used.